EFEKTIVITAS PROGRAM FIFA 11+ TERHADAP PENCEGAHAN CEDERA EKSTREMITAS BAWAH PADA PEMAIN SEPAK BOLA - Audy Fathia Khairunnisa; Alief Haekal Aditya; Erica Kholinne (Jurnal Akta Trimedika, 2024)
In sports, particularly in soccer players, injuries are common and generally involve the lower extremities, such as the ankles, knees, and leg muscles. One program developed to reduce injury risk is FIFA 11+, a warm-up program designed by the FIFA Medical Assessment and Research Centre (F-MARC) for injury prevention, especially in soccer players. The FIFA 11+ Program consists of a series of warm-up exercises aimed at improving core stabilization, muscle strengthening, proprioception training, and jumping techniques. This review study examines the effectiveness of the FIFA 11+ program in preventing lower extremity injuries in soccer players. The article shows that the FIFA 11+ program can reduce the risk of injury by up to 46.1% and decrease time lost due to injury by 28.6%. The program has been shown to improve peak knee extension torque as well as increase heart rate and core temperature. This can lead to enhanced blood flow and increased nerve receptor sensitivity, potentially improving muscle performance to reduce injury risk. Therefore, the FIFA 11+ program is an effective method for reducing injuries in soccer players. Although some studies mention insignificant effects on ankle stability, the program remains effective in overall injury prevention. The FIFA 11+ program is used as a simple, effective, and time-efficient injury prevention program that can replace other exercises. This training simultaneously targets various aspects.